2021
DOI: 10.1002/jgh3.12613
|View full text |Cite
|
Sign up to set email alerts
|

Ropeginterferon alfa‐2b in patients with genotype 1 chronic hepatitis C: Pharmacokinetics, safety, and preliminary efficacy

Abstract: Background and Aim Ropeginterferon alfa‐2b (P1101) is a novel long‐acting mono‐PEGylated recombinant proline interferon (IFN) conjugated to a 40 kDa branched polyethylene glycol (PEG) chain at its N‐terminus, allowing every‐two‐week injection. It received European Medicines Agency and Taiwan marketing authorization for the treatment of polycythemia vera in 2019 and 2020, respectively. This phase 2 study aimed to evaluate the pharmacokinetics, safety, and preliminary efficacy of ropeginterferon alfa‐2b as compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…In further clinical development, ropeginterferon alfa‐2b has been evaluated for the safety and efficacy for the treatment of HCV genotypes 1 and 2, 39,40 HBV 41 and polycythaemia vera 13–20,42,43 . Results of clinical trials in viral hepatitis showed that ropeginterferon alfa‐2b is as safe and effective as pegylated IFN alfa‐2a for the treatment of hepatitis B and C‐infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…In further clinical development, ropeginterferon alfa‐2b has been evaluated for the safety and efficacy for the treatment of HCV genotypes 1 and 2, 39,40 HBV 41 and polycythaemia vera 13–20,42,43 . Results of clinical trials in viral hepatitis showed that ropeginterferon alfa‐2b is as safe and effective as pegylated IFN alfa‐2a for the treatment of hepatitis B and C‐infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of polycythemia vera , which is a chronic myeloproliferative neoplasm, long-term and continuous treatment subcutaneously once every 2 weeks with ropeginterferon alfa-2b led to impressive hematological and clinical responses and was generally well tolerated [ 24 ]. Antiviral efficacy and good tolerability of ropeginterferon alfa-2b for the treatment of chronic HBV or HCV infections have also been demonstrated in several clinical studies [ 16 , 19 , 20 ]. Here, we report for the first time that a single subcutaneous administration of ropeginterferon alfa-2b showed promising clinical effect on COVID-19 patients with moderate disease, especially in younger patients who are ≤ 65 years old.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, ropeginterferon alfa-2b showed a favorable dosing schedule and safety profile in the treatment of chronic hepatitis including CHC and CHB. Two phase 2 clinical studies have been conducted to explore and validate the safety and efficacy of ropeginterferon alfa-2b in combination with ribavirin in the CHC treatment, including one in CHC genotype 1 and the other in CHC genotype 2 (Table 2) [10,11]. Abbreviation: CHC: chronic hepatitis C; SVR12: sustained virologic response at 12 weeks post-treatment; SVR12: sustained virologic response at 24 weeks post-treatment.…”
Section: Ropeginterferon Alfa-2b In Chronic Hepatitis C (Chc)mentioning
confidence: 99%
“…In the phase 2 CHC genotype 1 study [10], 106 treatment naive patients were enrolled and randomized into four treatment groups including peginterferon alfa-2a once every week SC at the dose of 180 µg (Group 1) as a control, ropeginterferon alfa-2b SC once every week at 180 or 270 µg (Group 2 and Group 3, respectively) or once every two weeks at 450 µg (Group 4), plus daily oral ribavirin for a treatment of 48 weeks [10]. Patients who were treated with ropeginterferon alfa-2b at 180 µg showed a notably higher serum exposure (AUC 0-τ ), which was 1.4-fold greater than those treated with peginterferon alfa-2a at the same dose.…”
Section: Ropeginterferon Alfa-2b In Chronic Hepatitis C (Chc)mentioning
confidence: 99%
See 1 more Smart Citation